The Attitude of Teachers towards Reflective Practice at College Level: A Mixed-Method Approach - Muhammad Zahid Hussain (International Islamic University Islamabad, 2020)
The purpose of this paper was to assess college teachers’ attitudes towards reflective practice and knowing their beliefs about promoting reflective practice to improve institutional and professional growth. The study was mixed-method in nature. The population was comprised of 203 college teachers and a sample of 132 teachers was randomly selected by using a sample selection table. An adapted Reflective Attitude Questionnaire (RAQ) constructed by Young (1989) consisting of 15 Likert items was used to assess the attitude of the college teachers. Semi structure interviews were also taken from the 10 college teachers to know their beliefs about how reflective practice could be promoted for teachers’ professional growth and institutional development. The RAQ had an alpha reliability of .90 which meant the instrument was reliable. Content validity was observed to verify the interview statements suggested by experts. Findings disclosed that teachers considered reflective practice useful for their teaching performance and professional growth. However, college principals did not facilitate reflection among teachers that impeded teachers' professional development as well as institutional growth.